Meneguhkan Peran Perempuan : (Harapan dan Keniscayaan Pragmatis) - Harjoni Harjoni (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2021)
Gender equality has been recognized and accepted as a normative framework for human development. The aim of this article is to explore in depth a pragmatic, action-based approach that will translate gender equality and women's empowerment programs into concrete reality. This study was carried out through action research in the Library Studies, in which the authors reviewed and analyzed gender-related studies for further conclusions to be drawn. The results of the study found that development goals regarding gender equality and women's empowerment are not only needed for sustainable development efforts in Indonesia; it also demands a pragmatic approach to appropriate policy formulation, program design, focused implementation and effective monitoring and evaluation in a climate of friendly political will, genuine commitment and a restoration of national orientation.